Desenvolvimento de circuitos planares sobre substratos têxteis - Cavalcante, Gustavo Araújo (2014)
The use of flexible materials for the development of planar circuits is one of the most desired and studied characteristics, lately, by researchers. This happens because the flexibility of the substrate can provide previously impracticable applications, due to the rigidity of the substrates normally used that makes it difficult to fit into the circuits in irregular surfaces. The constant interest in recent years for more lighter devices, increasingly more compacts, flexible and with low cost, led to a new line of research of great interest from both academic and technological views, that is the study and development of textile substrates that can be applied in the development of planar circuits, for applications in the areas of security, biomedical and telecommunications. This paper proposes the development of planar circuits, such as antennas , frequency selective surfaces (FSS) and planar filters, using textile (cotton ticking, jeans and brim santista) as the dielectric substrate and the Pure Copper Polyester Taffeta Fabric, a textile of pure copper, highly conductive, lightweight and flexible, commercially sold as a conductive material. The electrical characteristics of textiles (electric permittivity and loss tangent) were characterized using the transmission line method (rectangular waveguide) and compared with those found in the literature. The structures were analyzed using commercial software Ansoft Designer and Ansoft HFSS, both from the company Ansys and for comparison we used the Iterative Method of Waves (WCIP). For the purpose of validation were built and measured several prototypes of antennas, planar filters and FSS, being possible to confirm an excellent agreement between simulated and measured results